2015
DOI: 10.1108/jpbm-02-2014-0501
|View full text |Cite
|
Sign up to set email alerts
|

How are brand names of Chinese companies perceived by Americans?

Abstract: Drawing from prior research in psychology, linguistics and marketing, we conduct an experimental study of Americans' preferences for the English version of Chinese brand names. Specifically, we assess the impact of string length and semantic relevance to English on meaningfulness, memorability and likeability of brand names from Chinese companies. Design/methodology/approach: A 2x2 experimental design is used whereby brand names are categorized by string length (short vs. long) and semantic relevance to Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 77 publications
0
9
0
2
Order By: Relevance
“…The choice of students as sample members is common practice for studies involving an experimental design (Chaudhuri and Holbrook, 2001; Bluemelhuber et al , 2007, Fong et al , 2013; Chang et al , 2015). In addition, the product category involved is one which is also directly relevant to students, hence not compromising external validity (Lynch, 1982; Fetscherin et al , 2015). The study was conducted in Italy using a 2 (good/poor CR) × 2 (high/low CI) between-subjects factorial design, and thus questionnaires were randomly assigned to the respondents.…”
Section: Methodsmentioning
confidence: 99%
“…The choice of students as sample members is common practice for studies involving an experimental design (Chaudhuri and Holbrook, 2001; Bluemelhuber et al , 2007, Fong et al , 2013; Chang et al , 2015). In addition, the product category involved is one which is also directly relevant to students, hence not compromising external validity (Lynch, 1982; Fetscherin et al , 2015). The study was conducted in Italy using a 2 (good/poor CR) × 2 (high/low CI) between-subjects factorial design, and thus questionnaires were randomly assigned to the respondents.…”
Section: Methodsmentioning
confidence: 99%
“…Given the increasingly global nature of the markets, recent research has focused on the implications of using foreign brand names by Chinese companies in the USA (Fetscherin et al, 2015) and foreign-name brands in the USA and China (Villar et al, 2012). The appropriateness of choosing local versus global brands is a current branding concern (Lee et al, 2008), as exposure to global mass media has been found to influence the way that global brands are perceived (Frank and Watchravesringkan, 2016).…”
Section: The Increasingly Global Nature Of Marketsmentioning
confidence: 99%
“…Del mismo modo, el uso de nombres de lugar adquiere sentido cuando es congruente con la personalidad (imagen) del mismo (Pino, Guido y Peluso, 2015), aunque puedan suscitar aversion a su cambio (Hakala et al, 2015). Por otra parte, en casos concretos se evidencia que los nombres cortos y con relevancia semántica en inglés resultan más memorables (Fetscherin et al, 2015).…”
Section: Identidad Formalunclassified
“…Aunque se ha considerado que, tras consolidar una marca, el desarrollo natural pasaría por la expansión de la misma (Drawbaugh, 2001), las extensiones deberán contemplar unas condiciones genéricas: ser consistentes con la visión de marca, sostener y fortalecer la imagen de marca, ser consistentes con el posicionamiento global y prever la contingencia derivada de un impacto negativo por fallo de la extensión (Davis, 2002).…”
Section: Extensionesunclassified